Method for coating nickel powder with barium titanate

By forming a nickel oxide or sulfide inner shell on the surface of the nickel powder, and then covering a layer of barium titanate outer shell to form a double-shell structure of barium titanate coated nickel powder, the problems of easy oxidation of nickel electrodes and slurry shrinkage are solved, and the reliability and electrical performance of MLCC are improved.

CN119501080APending Publication Date: 2025-02-25JIANGSU BOQIAN NEW MATERIALS CO LTD

Patent Information

Application Number
CN202411842594.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

During the production of multi-layer ceramic capacitors (MLCCs), the nickel electrode is prone to oxidation, resulting in a decrease in conductivity, and the nickel slurry may shrink during the firing process, causing MLCC to warp and fracture.

Method used

The nickel powder is prepared by plasma heating evaporation condensation method, and an inner shell of nickel oxide or nickel sulfide is formed on its surface. Then a layer of barium titanate outer shell is coated by chemical liquid phase method to form a bi-shell structure of barium titanate coated nickel powder.

Benefits of technology

The nickel oxide or sulfide layer in the inner shell improves the bonding degree between the nickel powder and the dielectric material, improves the stability of the nickel powder during the firing process, and improves the reliability and electrical performance of MLCC.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119501080A_ABST
    Figure CN119501080A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of metal powder materials, and particularly relates to a method for coating nickel powder with barium titanate, which comprises the following steps: preparing an inner shell of nickel oxide and / or sulfide; dispersing the nickel powder with the inner shell in the dispersion liquid; sequentially adding a barium compound and a titanium compound into the dispersion liquid; the nickel powder with the inner shell and the barium compound and the titanium compound adsorbed on the surface is dried, and the barium compound and the titanium compound on the surface react to form a barium titanate coated outer shell; and dispersing the dried coated powder to form the barium titanate coated nickel powder with the double-shell structure. According to the nickel powder with the double-shell structure prepared by the technical scheme, the co-firing property of the nickel powder and a dielectric material is improved through the barium titanate shell of the outer shell, the combination degree of nickel and the dielectric material can be better improved through the nickel oxide and / or the nickel sulfide of the inner shell, and the dielectric property of the dielectric material is improved. Therefore, the yield of the nickel powder and the dielectric material in the process of preparing the electronic component is improved, and the electrical property of the electronic component is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal powder materials, and in particular relates to a coating method for barium titanate-coated nickel powder. Background Art

[0002] As the degree of miniaturization of electronic products continues to increase, electronic components are gradually moving towards miniaturization. The advantages of chip components such as small size, light weight, easy assembly and high reliability have also greatly improved the performance of electronic products.

[0003] Multilayer ceramic capacitors (MLCCs) are one of the most important chip passive devices in the modern electronics industry. They are known as the rice of the electronics industry and are widely used in consumer electronics, industrial electronics and modern military electronics. Traditional MLCC internal electrodes use precious metals such as silver and palladium. In addition to being expensive, their high-temperature co-firing, high resistivity and high melting point physical and chemical properties also affect their application in industrial devices. After entering the 1990s, nickel, as a base metal with good physical and chemical properties, has been widely used in MLCC internal electrodes.

[0004] Nickel is a high melting point metal that is not easily oxidized. When co-fired with the dielectric barium titanate at high temperatures, it will not be seriously oxidized, volatilized, or lost. When co-fired with the dielectric, it will not diffuse into the dielectric to affect the electrical insulation of the dielectric material. It also has many characteristics such as easy size control and good dispersibility. However, when nickel powder is used alone in the MLCC production process, the following problems still exist: nickel electrodes are prone to oxidation and lose their good conductivity, and nickel paste shrinks during the firing process, causing MLCC warping and fracture.

[0005] Barium titanate (BaTiO3) is a lead-free piezoelectric ceramic material discovered in the early 20th century. It has excellent high dielectric, low loss characteristics, and excellent piezoelectric and ferroelectric properties. It is widely used in MLCC, PTC and other fields, becoming one of the raw materials for electronic ceramics and is known as the "pillar of the electronic ceramics industry." The earliest industrial coating method for BaTiO3 powder is the solid phase method, which uses BaCO3 and TiO2 as raw materials. After ball milling to fully mix the raw materials, they are calcined at a temperature above 1000 ° C to synthesize BaTiO3 powder. The chemical equation for this process is:

[0006] BaCO3+TiO2→BaTiO3+CO2↑.

[0007] BaTiO3 is a consistent melting compound with a melting point of 1618 ℃, and its crystal structure will also change with the change of temperature. In the temperature range from 1460 ℃ to the melting point, its crystal structure is a hexagonal system, which is a stable phase, and crystal growth must be carried out below 1460 ℃. When the temperature is between 130 and 1460 ℃, the crystal structure is a cubic phase system, at which time the BaTiO3 crystal structure has the highest symmetry, so there is no ferroelectricity and piezoelectricity; in the temperature range of 0 to 130 ℃, BaTiO3 undergoes a paraelectric-ferroelectric phase transition, the crystal symmetry decreases, and it changes from a cubic system to a tetragonal system with ferroelectricity, at which time its ferroelectric and dielectric properties are the best; at -90 to 0 ℃, it changes to an orthorhombic system (monoclinic system), and the ferroelectricity does not disappear; when the temperature drops below -90 ℃, the BaTiO3 crystal structure changes to a trigonal system. Under normal circumstances, the room temperature dielectric constant of BaTiO3 ceramics is about 2400; when the temperature reaches the Curie point of BaTiO3, its dielectric constant will increase rapidly to about 10000. This characteristic of BaTiO3, coupled with its inherent high dielectric constant and low dielectric loss, makes it the preferred dielectric material in MLCC manufacturing.

[0008] Coating a BaTiO3 ceramic layer on the surface of Ni powder can effectively improve its sintering performance and antioxidant properties. First, the introduction of pure BaTiO3 ceramic coating material can avoid the incorporation of other substances besides the core material components of MLCC, and will not have an adverse effect on the internal electrode slurry and the performance of MLCC products; secondly, the BaTiO3 ceramic coating layer can improve the compatibility of the Ni electrode with the BaTiO3 ceramic dielectric layer during the sintering process, and improve the reliability of MLCC. The current coating method of BaTiO3 coated Ni powder focuses on the liquid phase method, and the BaTiO3 coating layer is prepared by chemical reaction. Patent CN101774028A relates to BaTiO3 coated Ni powder and its coating method. This invention uses ultrasonic spray thermal decomposition to prepare composite powder. This method belongs to the chemical method. The addition of more chemical substances during the preparation process may have a negative impact on the subsequent slurry preparation. In addition, this method also has problems such as poor sphericity of the composite powder.

[0009] Patent CN103508736A relates to BaTiO3 coated Ni powder and its coating method. This invention adopts chemical hydrothermal crystallization method to prepare composite powder, and the sintering performance and antioxidant performance of powder product are improved to a certain extent. In the process of preparing single oxide (Cr2O3, or TiO2, or ZrO2) coated Ni powder by physical vapor phase method, the raw material is single, the process is simple and easy to control, and only the composition ratio between single oxide and Ni raw material is involved. However, in the coating process of multi-oxide system, there are melting, decomposition, evaporation of multiple oxide raw materials, and co-evaporation of Ni metal raw materials. The difference in evaporation rate of different raw materials makes it difficult to control the composition of powder product, and the composition, crystal structure and thickness of coating layer are difficult to control. These problems are solved in the present invention.

[0010] The DC arc plasma method is a physical vapor phase method for preparing core-shell type micro-nano composite powder materials. Its advantages are that it uses bulk raw materials, can be prepared on a large scale, has no chemical pollution, and is easy to control power and preparation atmosphere. Patent CN118847991 uses the DC arc plasma co-evaporation method to prepare core-shell BaTiO3 coated Ni powder materials in situ. On the basis of single oxide coated metal micro-nano powders, it further develops the preparation technology of multi-oxide ceramic material coated metal particles, realizes the preparation of complex oxide coated metal particles and their structural control. Compared with the conventional chemical solution method, it has the advantages of in-situ coating, rich raw material sources, high sphericity of powder products, no by-products, no chemical pollution, and easy scale-up.

[0011] However, in actual applications, it was found that whether the composite powder prepared by the hydrothermal crystallization method or the in-situ coated powder prepared by the DC plasma method, problems such as easy peeling of the coating shell, uneven coating, and loose bonding between the coating layer and nickel would occur. During the use of the slurry, there are still problems such as poor co-firing and warping. Summary of the invention

[0012] The object of the present invention is to provide a coating method for preparing barium titanate-coated nickel powder. The prepared barium titanate-coated nickel powder is a double-shell structure powder, which is used to solve the problem of shrinkage rate of inner electrode nickel powder and ceramic dielectric mismatch during co-sintering of MLCC metal inner electrode and ceramic dielectric layer. An inner shell of nickel oxide and / or nickel sulfide is arranged on the surface of nickel powder, and a barium titanate outer shell is arranged on the outer layer of the inner shell. The transition of the inner shell can enhance the bonding force between the inner core and the outer shell, and improve the stability of nickel in the inner electrode slurry during the firing process.

[0013] To achieve the above objectives, this application is implemented through the following technical solutions:

[0014] A coating method for barium titanate coated nickel powder, wherein the barium titanate coated nickel powder has a nickel powder core with a specific surface area equivalent particle size d of 30 to 600 nm; the surface has a double shell structure, the inner shell layer is nickel oxide and / or sulfide, and the outer shell is barium titanate, and the coating method is:

[0015] S1. Preparing a core nickel powder having a specific surface area equivalent particle size of 30 to 600 nm by a plasma heating evaporation condensation method, pre-oxidizing and / or pre-sulfurizing the core nickel powder, so that the surface of the core nickel powder contacts oxygen or sulfur elements to prepare an inner shell of nickel oxide and / or sulfide;

[0016] S2, dispersing the nickel powder with an inner shell in a dispersion liquid by a chemical liquid phase method;

[0017] S3, adding barium compound and titanium compound to the dispersion successively;

[0018] S4, drying the nickel powder with an inner shell on which barium compounds and titanium compounds are adsorbed, and the barium compounds and titanium compounds on the surface react to form a barium titanate-coated outer shell;

[0019] S5. Dispersing the dried coated powder to form the barium titanate coated nickel powder having a double shell structure.

[0020] Furthermore, in step S1, a core nickel powder is first prepared by a plasma heating evaporation condensation method, and then the surface of the nickel powder is contacted with oxygen and / or sulfur elements to form an oxide layer and / or a sulfide layer.

[0021] Furthermore, in step S1, the nickel powder having a surface oxide layer and / or a sulfide layer is further mixed and contacted with oxygen and / or sulfur elements in a heating furnace, and a slow reaction is carried out at a temperature between 120 and 350 degrees Celsius for not less than 15 minutes to prepare a strengthened inner shell.

[0022] Furthermore, in step S3, the barium compound is at least one of barium acetate, barium carbonate, and barium hydroxide, and the titanium compound is at least one of tetrabutyl titanate, titanium sulfate, titanium hydroxide, hydrated titanium dioxide, and titanium alkoxide.

[0023] Furthermore, in step S3, the dispersion process temperature is controlled between 10 and 95°C, the barium compound is first added to the dispersion and fully mixed with the nickel powder, and then the titanium compound is added by solution titration; or the titanium compound is first added to the dispersion and fully mixed with the nickel powder, and then the barium compound is added by solution titration.

[0024] Furthermore, in step S5, spray drying is used, and dispersion is performed by ball milling or air flow dispersion.

[0025] Furthermore, the average inner shell thickness of the prepared barium titanate-coated nickel powder is 1 to 25 nm, and the average outer shell thickness is 0.5 to 12.5 nm; the outer shell layer is one of the discontinuously distributed porous, dot-shaped, and island-shaped barium titanate coatings.

[0026] Furthermore, the proportion of the barium titanate in the outer shell layer covering the surface of the inner shell layer is greater than 50%.

[0027] Furthermore, in the inner shell layer of the prepared barium barate-coated nickel powder, the oxide and / or sulfide is at least one of nickel oxide, nickel sulfide, nickel hydroxide and nickel carbonate.

[0028] Furthermore, the core nickel powder of the prepared barium barate-coated nickel powder has a discrete distribution, and the discreteness is R=Dmax-Dmin>d, wherein Dmax is the particle size of the largest particle among 10,000 particles continuously counted in any SEM photo, and Dmin is the particle size of the smallest particle among 10,000 particles continuously counted in any SEM photo.

[0029] The beneficial effects of the present invention are:

[0030] The coating method of barium titanate-coated nickel powder disclosed in the present invention can prepare nickel powder with a double-shell structure. In addition to improving the co-firing property of nickel powder and dielectric materials through the barium titanate shell of the outer shell, the bonding degree between nickel and dielectric materials can be better improved through the nickel oxide and / or nickel sulfide of the inner shell, so as to improve the yield rate of the nickel powder and the dielectric materials in the process of preparing electronic components and improve the electrical performance of the electronic components. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a SEM photo of the barium barate-coated nickel powder prepared in the present invention. DETAILED DESCRIPTION

[0032] The technical solution of the present invention is described in detail below through examples. The following examples are merely exemplary and can only be used to explain and illustrate the technical solution of the present invention, but cannot be construed as limiting the technical solution of the present invention.

[0033] The present application provides a coating method for barium titanate coated nickel powder, wherein the barium titanate coated nickel powder has a nickel powder core with a specific surface area equivalent particle size d of 30 to 600 nm; its surface has a double shell structure, the inner shell layer is nickel oxide and / or sulfide, and the outer shell is barium titanate, and the coating method is:

[0034] S1. A core nickel powder having a specific surface area equivalent particle size of 30 to 600 nm is prepared by a plasma heating evaporation condensation method, and the core nickel powder is pre-oxidized and / or pre-sulfurized so that the surface of the core nickel powder contacts oxygen or sulfur elements to prepare an inner shell of nickel oxide and / or sulfide.

[0035] S2. Dispersing the nickel powder with an inner shell in a dispersion liquid by a chemical liquid phase method.

[0036] S3. Adding barium compound and titanium compound to the dispersion successively. In the present application, there is no requirement for the usage ratio of barium compound and titanium compound, and those skilled in the art can make corresponding adjustments according to the design requirements.

[0037] S4. Drying the nickel powder with an inner shell on which barium compounds and titanium compounds are adsorbed, and the barium compounds and titanium compounds on the surface react to form a barium titanate-coated outer shell.

[0038] S5. Dispersing the dried coated powder to form the barium titanate coated nickel powder having a double shell structure.

[0039] In the present application, in step S1, a core nickel powder is first prepared by a plasma heating evaporation condensation method, and then the surface of the nickel powder is exposed to oxygen and / or sulfur to form an oxide layer and / or a sulfide layer.

[0040] In the present application, in step S1, the nickel powder having a surface oxide layer and / or a sulfide layer is further mixed and contacted with oxygen and / or sulfur elements in a heating furnace, and a slow reaction is carried out for not less than 15 minutes at a temperature between 120 and 350 degrees Celsius to prepare a strengthened inner shell.

[0041] In the present application, in step S3, the barium compound is at least one of barium acetate, barium carbonate, and barium hydroxide, and the titanium compound is at least one of tetrabutyl titanate, titanium sulfate, titanium hydroxide, hydrated titanium dioxide, and titanium alkoxide.

[0042] In the present application, in step S3, the temperature of the dispersion process is controlled between 10 and 95°C, the barium compound is first added to the dispersion liquid and fully mixed with the nickel powder, and then the titanium compound is added by solution titration; or the titanium compound is first added to the dispersion liquid and fully mixed with the nickel powder, and then the barium compound is added by solution titration.

[0043] In the present application, in step S5, spray drying is used, and dispersion is performed by ball milling or air flow dispersion.

[0044] In the present application, the average inner shell thickness of the prepared barium titanate-coated nickel powder is 1 to 25 nm, and the average outer shell thickness is 0.5 to 12.5 nm; the outer shell layer is one of the discontinuously distributed porous, dot-shaped, and island-shaped barium titanate coatings.

[0045] In the present application, the proportion of the barium titanate of the outer shell layer covering the surface of the inner shell layer is greater than 50%.

[0046] In the present application, in the inner shell layer of the prepared barium barate-coated nickel powder, the oxide and / or sulfide is at least one of nickel oxide, nickel sulfide, nickel hydroxide, and nickel carbonate.

[0047] In the present application, the core nickel powder of the prepared barium barate-coated nickel powder has a discrete distribution, and the discreteness is R=Dmax-Dmin>d, wherein Dmax is the particle size of the largest particle among 10,000 particles counted continuously in any SEM photo, and Dmin is the particle size of the smallest particle among 10,000 particles counted continuously in any SEM photo.

[0048] Example 1

[0049] Nickel powder with an equivalent particle size of 568 nm according to specific surface area was prepared by plasma heating evaporation condensation method. The powder was surface oxidized by passing through a tube furnace so that the thickness of its oxide layer was 17 nm, and a powder with an inner shell of the oxide layer was prepared.

[0050] Stir and disperse n-butanol, water and hexadecyl ammonium bromide into a dispersion liquid. In this embodiment, the dosage ratio of n-butanol, water and hexadecyl ammonium bromide is not specifically required. Then, nickel powder with an inner shell layer is added to the dispersion liquid to form a mixed liquid with a solid content of 35%, and the mixture is dispersed by an emulsifier and ultrasonic wave for 30 minutes.

[0051] The temperature of the dispersion process was controlled between 40 and 45°C, and a mixture of tetrabutyl titanate and n-butyric acid in a mass ratio of 1:1 was added to the dispersion at a rate of 5 L / min. After the addition was completed, the stirring reaction was continued for 30 min.

[0052] After filtering the above mixture, add it into water and continue to stir and disperse it, and add a 5% weight concentration of barium acetate aqueous solution at a rate of 1 L / min. After the addition is completed, continue to stir for 30 min.

[0053] The powder aqueous solution with a double-shell structure is then filtered or precipitated, spray-dried, and then subjected to dry powder dispersion treatment by air jet milling to obtain barium titanate-coated nickel powder with a double-shell structure.

[0054] The prepared barium titanate-coated nickel powder has a discreteness meter of R=Dmax-Dmin>d, where Dmax is the particle size of the largest particle among 10,000 particles continuously counted in any SEM photograph, which is 2150 nm, and Dmin is the particle size of the smallest particle among 10,000 particles continuously counted in any SEM photograph, which is 132 nm. The outer shell layer is a discontinuously distributed porous barium titanate coating, and the proportion of the barium titanate coating on the outer shell layer to the inner shell layer surface is 97%.

[0055] Example 2

[0056] Nickel powder with an equivalent particle size of 360 nm according to the specific surface area was prepared by plasma heating evaporation condensation method. The powder was surface-sulfurized in a tube furnace so that the thickness of the sulfide layer was 13 nm, and then the powder with an inner shell of the sulfide layer was prepared.

[0057] Stir and disperse n-butanol, water and hexadecyl ammonium bromide into a dispersion. In this embodiment, the ratio of n-butanol, water and hexadecyl ammonium bromide is 2:3:1. Then, add the nickel powder with an inner shell layer into the dispersion to form a mixed solution with a solid content of 40%, and disperse it by emulsifier and ultrasonic double dispersion for 30 minutes.

[0058] The temperature of the dispersion process was controlled between 40 and 45 °C, and a mixture of tetrabutyl titanate and n-butyric acid in a mass ratio of 1:1 was added to the dispersion at a rate of 5 L / min. After the addition was completed, the stirring reaction was continued for 30 min.

[0059] After filtering the above mixture, add it into water and continue to stir and disperse it, and add a 5% weight concentration of barium acetate aqueous solution at a rate of 1 L / min. After the addition is completed, continue to stir for 30 min.

[0060] The powder aqueous solution with a double-shell structure is then filtered or precipitated, spray-dried, and then subjected to dry powder dispersion treatment by air jet milling to obtain barium titanate-coated nickel powder with a double-shell structure.

[0061] The prepared barium titanate-coated nickel powder has a dispersion meter of R=Dmax-Dmin>d, where Dmax is the particle size of the largest particle in 10,000 particles continuously counted in any SEM photo, which is 1860 nm, and Dmin is the particle size of the smallest particle in 10,000 particles continuously counted in any SEM photo, which is 124 nm. The outer shell is a non-continuously distributed porous barium titanate coating, and the proportion of the barium titanate-coated inner shell surface in the outer shell is 95%. It has been tested that the average thickness of the barium titanate shell in the barium titanate-coated nickel powder is 11.5 nm.

[0062] Example 3

[0063] Nickel powder with an equivalent particle size of 440 nm according to specific surface area was prepared by plasma heating evaporation condensation method. The powder was surface oxidized and sulfurized in a tube furnace so that the total thickness of the oxidation and sulfurization layers was 23 nm. The powder with an inner shell of oxidation and sulfurization layers was then added. The sulfur element accounted for 0.13% of the total mass of the powder by weight. The oxides mainly included nickel oxide, and the sulfides included nickel sulfide.

[0064] Stir and disperse n-butanol, water and hexadecyl ammonium bromide into a dispersion liquid. In this embodiment, the ratio of n-butanol, water and hexadecyl ammonium bromide is 2:3:1. Then, nickel powder with an inner shell layer is added to the dispersion liquid to form a mixed liquid with a solid content of 44%, and the mixture is dispersed by an emulsifier and ultrasonic waves for 30 minutes.

[0065] The temperature of the dispersion process was controlled between 40 and 45°C, and a mixture of tetrabutyl titanate and n-butyric acid in a mass ratio of 1:1 was added to the dispersion at a rate of 5 L / min. After the addition was completed, the stirring reaction was continued for 30 minutes.

[0066] After filtering the above mixture, add it into water and continue to stir and disperse it, and add a 7% weight concentration of barium carbonate aqueous solution at a rate of 1 L / min. After the addition is completed, continue to stir for 30 minutes.

[0067] The powder aqueous solution with a double-shell structure is then filtered or precipitated, spray-dried, and then subjected to dry powder dispersion treatment by air jet milling to obtain barium titanate-coated nickel powder with a double-shell structure.

[0068] The prepared barium titanate-coated nickel powder has a dispersion meter of R=Dmax-Dmin>d, where Dmax is the particle size of the largest particle in 10,000 particles continuously counted in any SEM photo, which is 2030 nm, and Dmin is the particle size of the smallest particle in 10,000 particles continuously counted in any SEM photo, which is 126 nm. The outer shell layer is a discontinuously distributed porous barium titanate coating, and the proportion of the barium titanate coating on the inner shell surface is 53%, and the average thickness of the outer shell barium titanate coating is 5nm.

[0069] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A coating method for barium titanate coated nickel powder, characterized in that: The barium titanate coated nickel powder has a nickel powder core with a specific surface area equivalent particle size d of 30 to 600 nm; its surface has a double shell structure, the inner shell is nickel oxide and / or sulfide, and the outer shell is barium titanate, and the coating method is: S1. Preparing a core nickel powder having a specific surface area equivalent particle size of 30 to 600 nm by a plasma heating evaporation condensation method, pre-oxidizing and / or pre-sulfurizing the core nickel powder, so that the surface of the core nickel powder contacts oxygen or sulfur elements to prepare an inner shell of nickel oxide and / or sulfide; S2, dispersing the nickel powder with an inner shell in a dispersion liquid by a chemical liquid phase method; S3, adding barium compound and titanium compound to the dispersion successively; S4, drying the nickel powder with an inner shell on which barium compounds and titanium compounds are adsorbed, and the barium compounds and titanium compounds on the surface react to form a barium titanate-coated outer shell; S5. Dispersing the dried coated powder to form the barium titanate coated nickel powder having a double shell structure.

2. The coating method of barium titanate coated nickel powder according to claim 1, characterized in that: In step S1, a core nickel powder is first prepared by a plasma heating evaporation condensation method, and then the surface of the nickel powder is exposed to oxygen and / or sulfur to form an oxide layer and / or a sulfide layer.

3. The coating method of barium titanate coated nickel powder according to claim 1, characterized in that: In step S1, the nickel powder having a surface oxide layer and / or a sulfide layer is further mixed and contacted with oxygen and / or sulfur elements in a heating furnace, and a slow reaction is performed at a temperature between 120 and 350 degrees Celsius for not less than 15 minutes to prepare a reinforced inner shell.

4. The coating method of barium titanate coated nickel powder according to claim 1, characterized in that: In step S3, the barium compound is at least one of barium acetate, barium carbonate and barium hydroxide, and the titanium compound is at least one of tetrabutyl titanate, titanium sulfate, titanium hydroxide, hydrated titanium dioxide and titanium alkoxide.

5. The coating method of barium titanate coated nickel powder according to claim 1, characterized in that: In step S3, the dispersion process temperature is controlled between 10 and 95°C, the barium compound is first added to the dispersion and fully mixed with the nickel powder, and then the titanium compound is added by solution titration; or the titanium compound is first added to the dispersion and fully mixed with the nickel powder, and then the barium compound is added by solution titration.

6. The coating method of barium titanate coated nickel powder according to claim 1, characterized in that: In step S5, spray drying is used, and dispersion is performed by ball milling or air flow dispersion.

7. The coating method of barium titanate coated nickel powder according to claim 1, characterized in that: The average inner shell thickness of the prepared barium titanate-coated nickel powder is 1-25 nm, and the average outer shell thickness is 0.5-12.5 nm; the outer shell layer is one of the discontinuously distributed porous, dot-shaped, and island-shaped barium titanate coatings.

8. The coating method of barium titanate coated nickel powder according to claim 7, characterized in that: The proportion of the barium titanate of the outer shell layer covering the surface of the inner shell layer is greater than 50%.

9. The coating method of barium titanate coated nickel powder according to claim 1, characterized in that: In the inner shell layer of the prepared barium barate-coated nickel powder, the oxide and / or sulfide is at least one of nickel oxide, nickel sulfide, nickel hydroxide and nickel carbonate.

10. The coating method of barium titanate coated nickel powder according to claim 1, characterized in that: The core nickel powder of the prepared barium barate coated nickel powder has a discrete distribution, and according to the discreteness meter R=Dmax-Dmin>d, the Dmax is the particle size of the largest particle among 10,000 particles continuously counted in any SEM photo, and Dmin is the particle size of the smallest particle among 10,000 particles continuously counted in any SEM photo.

Citation Information

Patent Citations

  • Method for preparing Ni-BaTiO3 compound powder

    CN101774028A

  • Barium titanate coated nanometer nickel powder for inner electrode of MLCC (Multilayer Ceramic Capacitor) and preparation method thereof

    CN103508736A

Cited By

  • Barium titanate coated Ni particle material synthesized with assistance of spray drying technology and method of barium titanate coated Ni particle material

    CN119634725A

  • A spray drying technique assisted synthesis of barium titanate coated nickel particles material and method thereof

    CN119634725B